EFFECT OF MULCHING AND LICORICE ROOT EXTRACT ON GROWTH OF TWO BROCCOLI CULTIVARS (BRASSICA OLERACEA VAR. ITALICA.) - YOUSIF , KURDISTAN HASSAN; SAEID, ABDUL JEBBAR IHSAN (Journal of Duhok University, 2022)
This study was aimed to evaluate the effect of cultivars, mulching, foliar application of licorice root extract, on broccoli leaves (Brassica oleracea var. italica). The findings demonstrated that both cultivars Wisdom and Agassi have significant differences in terms of vegetative growth characters, All studied traits in both cultivars were significantly increased by the wisdom cultivar during the study seasons. It was also observed that plastic mulch significantly increased all investigated traits in both cultivars. The interactions between licorice root extract and straw were marked by the elevation of most detected traits. Black plastic mulch significantly impacted most measures, whereas 18g.L-1 and black plastic mulch together produced the greatest overall result in all vegetative growth parameters (Number of leaf. plant-1, plant high (cm), stem length (cm) , branch number. Plant-1 and chlorophyll contents (SPAD). Regarding nutrients contents, significant differences were showed. The combination among three factures was significant enhanced all studied traits